Accelerating sustainable energy transition(s) in developing countries the challenges of climate change and sustainable development - Delina, Laurence L. (Routledge studies in energy transitions, 2018)
This book explores how the transitions occur in fourteen developing countries and broadly surveys their technological, policy, financing, and institutional capacities in response to the three key aspects of energy transitions: achieving universal energy access, harvesting energy efficiency, and deploying renewable energy. This book will be of interest to students and scholars of energy and climate policy, development studies, international relations, politics, strategic studies, and geography. It is also useful to policymakers and development practitioners.